From inner-bay preservation to offshore dissipation: Spatiotemporal patterns and tracing of pharmaceuticals in Shenzhen Bay of the greater bay area, South China - Guangyang Cheng; Haoshuai Li; Lei Xing; Yang Zhou; Danxu Guo; Zimin Wang; Siqi Zhao; Zongshan Zhao; Shuhong Fang; Fang Chen; Rui Bao (Marine Pollution Bulletin, 2026)

Enhancing transportation system resilience under earthquake-induced geohazards: a framework for cross-regional rescue - Damin Zhou; Li Peng; Rui Guo; Zhousong Jiang; Muzi Li (Transportation Research Part D: Transport and Environment, 2026)

Nonradical pathway in peroxymonosulfate-based Fenton-like reactions triggered by the active Fe-Cu dual sites encapsulated in endogenous N-rich biochar - Rui Yang; Chaoting Jiang; Wangbo Wang; Xianshu Zhou; Fangshu Xie; Mingming Ta; Tuo Wang; Haifang Cai; Juan Guo; Weihuang Zhu (Journal of Environmental Chemical Engineering, 2026)

Spatio-temporal-functional assembly of Daqu microbiome: Mechanistic insights and quality improvement - Rui Ma; Xiaojie Nan; Yanting Li; Yuanyu Su; Mingxia Cheng; Yujie Zhang; Yang Cui; Qiong Zhou; Jingang Gu; Shang Guo (Food Research International, 2026)

From charge dependence to host-guest recognition: A reliable CZE method for simultaneous separation and determination of flavonoid glycosides with similar structures - Rui Zhang; Biying Guo; Xin Zhou; Fuyu Yang; Yong Xu (Food Chemistry, 2026)

Solvent-triggered dissolution-gelation for multiscale structural densification of lignocellulosic biocomposites - Yifan Guo; He Zhang; Tongxin Bian; Xiufang Ma; Xiu Dong; Rui Fan; Wei Wei; Yun Wan; Bin Yang; Zuowan Zhou (Chemical Engineering Journal, 2026)

Corrigendum to “Evaluation of street-scale air pollution using multi-source data fusion” [Sustainable Cities and Society 148 (2026) 107644] - Zhihao Guo; Xun Zhang; Zongning Wu; Rui Zhou; Xiansheng Liu; Jin Zou (Sustainable Cities and Society, 2026)

Evaluation of street-scale air pollution using multi-source data fusion - Zhihao Guo; Xun Zhang; Zongning Wu; Rui Zhou; Xiansheng Liu; Jin Zou (Sustainable Cities and Society, 2026)

Electronic structure engineering of 2D Ni-MOF/CNTs for glucose monitoring and energy supply in a wearable sweat sensor system - Rui-Dong Shi; Guo-Tao Xiang; Tao Cheng; Zi-Dong Zhou; Na Chen; Raul D. Rodriguez; Jin-Ju Chen (Chemical Engineering Journal, 2026)

Influence of Suspended Carriers on Pollutants Removal by Multi-tank A/O Process - Kai Ma; Rui Min; Shuai Guo; Yu Kang; Tianhong Zhou (Water, Air, & Soil Pollution, 2026)

Near-real-time mapping for causal agents of forest disturbances in China using harmonized Landsat and Sentinel-2 dataset - Ronghua Liao; Chengcheng Guo; Lingkun Chen; Yulin Jiang; Yuchen Tao; Jiani Liao; Rui Lu; Huaguo Huang; Zhou Shi; Su Ye (Remote Sensing of Environment, 2026)

Remote sensing of rural clean heating impacts on air quality: An STL-Q3 framework in Henan Province, China - Yongliang Yang; Wenqiang Guo; Zhitao Zhou; Kai Ji; Zhibin Lai; Rui Xu; Feiyang Wang; Linlu Mei (Remote Sensing Applications: Society and Environment, 2026)

Chitosan composite packaging film loaded with luteolin-superoxide dismutase nano-micelles: Enhancing food preservation performance - Pei Wu; Yilin Che; Rui Zhou; Yixin Tang; Lei Guo; Baiqiao Chen; Xinran Yan; Shanli Wu; Chang Liu; Mujie Kan; Jizhou Zhang; Xi Yang; et al. (Food Research International, 2026)

Increasing carbon emissions despite declining burned area in the Northern Hemisphere wildfires - Rui Shi; Yuhui He; Ruitong Guo; Xiaofan Wang; Yaliang Hou; Yue Zhou; Xiaoying Niu; Hui Wen; Jun Liu; Wei Pu; Xin Wang; Dongyou Wu (Atmospheric Research, 2026)

Single-cell transcriptomic analysis identifies a MIF-driven keratinocyte-macrophage-Th2 axis as a key inflammatory circuit in atopic dermatitis - Yan Wei; Rui-Min Bai; Hao-Ran Guo; Jin Shan; Li-Juan Wang; Yan Zhou; Kuan-Hou Mou; Yan Zheng; Ya-Guang Zhang (Inflammation Research, 2026)

A root cause diagnosis strategy based on error correction instantaneous granger causality algorithm for non-stationary industrial processes - Rui Chen; Yuan-Qiang Zhou; Li-Lan Liu; Jian-Guo Wang; Yuan Yao; Chen Peng (Process Safety and Environmental Protection, 2026)

Ascosphaeraapis LncRNA6140 promotes the infection of honeybee larvae through the milR5658-x–ATPase axis - Jianfeng Qiu; Tao Wu; Shuai zhou; Nian Fan; Genchao Gan; Zhitan Liu; Zhongmin Fu; Rui Guo; Dafu Chen (Insect Biochemistry and Molecular Biology, 2026)

The impact of ultra-high pressure processing on crayfish tropomyosin allergenicity and microstructure preservation: Insights into texture and flavors - Rui Liu; Yang Guo; Xuening Yu; Wensi Xu; Xiaoyang Liu; Dayong Zhou (Food Chemistry, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Adaptive Fixed-Time Control Framework for Deterministic Response of Fully Constrained Vessels with Unknown Dynamics - Qiang Guo; Shuangpeng Duan; Jia Zhou; Shengguo Wang; Rui Li; Xianku Zhang (Journal of Marine Science and Engineering, 2026)
To achieve precise trajectory tracking for surface vessels subject to unknown dynamics, strict physical limitations, and external disturbances, this paper proposes an Adaptive Fixed-Time Control Framework that ensures a deterministic response under full constraints. First, navigation safety is guaranteed by employing a Barrier Lyapunov Function (BLF) to strictly confine vessel position states, enabling constrained position tracking without requiring prior knowledge of the desired trajectory. Second, addressing the input constraint aspect of the “full constraints” problem, a fixed-time auxiliary system is introduced to compensate for nonlinearities induced by actuator saturation, thereby maintaining control feasibility. Central to this framework is the realization of a deterministic response; by incorporating fixed-time convergence theory, the controller guarantees that velocity tracking errors converge within a predefined time bound independent of initial conditions. Furthermore, an RBF neural network combined with adaptive techniques is utilized to estimate unknown dynamics and external disturbance bounds online, enhancing robustness and safety in realistic marine environments.

Optimizing drug delivery in smart pharmacies: a novel framework of multi-stage grasping network combined with adaptive robotics mechanism - Rui Tang; Shirong Guo; Yuhang Qiu; Honghui Chen; Lujin Huang; Ming Yong; Linfu Zhou; Liquan Guo (Medical & Biological Engineering & Computing, 2026)

Exposure to per- and polyfluoroalkyl substances and risk of reproductive system cancers: A systematic review and meta-analysis - Xin Liu; Zhihong Lv; Zixiang Huang; Rui Sun; Dingyu Zhu; Pengcheng Xu; Yiquan Xiong; Xiaowei Guo; Yaxuan Ren; Junhua Zhou (Journal of Environmental Health Science and Engineering, 2026)

Triphasic volatile emission dynamics and gene expression in postharvest PGF-lost non-melting peach (Prunus persica) var. RedY - Ping Zhou; Xiaodan Zhang; Xin Feng; Rui Guo; Shaobin Yan; Xiuqing Wei; Liang Li; Yajun Tang; Zhizheng Fang; Yan Lei (Postharvest Biology and Technology, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

Dominant drivers of soil multifunctionality change: interactions among soil, plants, and the atmosphere - Tiantian Luo; Weiyi Zhou; Yun Shi; Fenghong Zhang; Guo Rui; Hongyuan He; Tao Wu; Hongxia Li; Yiting Ma (Plant and Soil, 2026)

A room-temperature wireless NO2 gas sensor enabled by WO3 modified V2CTx nanosheets - Haineng Bai; Rui Guo; Yixin Zhou; Cheng Feng; Yiru Chen; Shengjie Zhang; Yamin Feng; Weifeng Liu; Kuili Liu; Fuqiang Guo; Jin Wang; Dunjun Chen; et al. (Chemical Engineering Journal, 2026)

Evaluating the environmental impact of hydrothermal cracking solid organic fertilizer: Carbon and nitrogen retention and toxic metals analysis - Rui Xia; Xiao-xiao Yang; Jue Wang; Kai-le Li; Zhi-peng Sun; Qing-hai Li; Hui Zhou; Yan-guo Zhang (Journal of Environmental Sciences, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

Response of soil conservation functions to vegetation dynamics and restoration potential on the Loess Plateau - Xiaoxue Guo; Peng Tian; Guangju Zhao; Peng Gao; Chaohui Ma; Rui Shan; Jiahui Zhou; Xingmin Mu (CATENA, 2026)

Genomic evidence resolves species identity and hybridization in farmed Golden pompano (Trachinotus anak) - Liang Guo; Siqing Wang; Jiehong Wei; Rui Peng; Zhongyuan Shen; Luojing Zhou; Jiaxuan Kang; Ke Rao; Yang Yang; Zhennian Chen; Chang Wu (Aquaculture, 2026)

Corrigendum to “Silica nanoparticles induce cardiac injury and dysfunction via ROS/Ca2+/CaMKII signaling” [Sci. Total Environ., 837 (2022), 155733] - Yi Qi; Hailin Xu; Xueyan Li; Xinying Zhao; Yan Li; Xianqing Zhou; Rui Chen; Yanbo Li; Zhiwei Sun; Caixia Guo (Science of The Total Environment, 2026)

Ultra-high pressure processing modifies crayfish (Procambarus clarkii) texture, flavor, and tropomyosin allergenicity: Elucidating pressure-dependent structure-function relationships - Rui Liu; Yang Guo; Xuening Yu; Xiaoyang Liu; Dayong Zhou (Food Research International, 2026)

Biocarrier with layer-specific structure enhanced the microalgae-partial nitrification-anammox system performance: Insights into microbial aggregation behavior by FT-ICR-MS and XDLVO analysis - Xue Chen; Rui Hu; Jiabang Li; Yuchen Guo; Youfei Zhou; Meilan Zhang; Guihua Zhuo; Xueqin Lu; Guangyin Zhen (Chemical Engineering Journal, 2026)

Understanding the migration and transformation characteristics of Cr3+ in the hydrothermal cracking of biomass model components - Rui Xia; Kai-le Li; Peng Zhao; Xiao-xiao Yang; Jue Wang; Ke-wen An; Qing-hai Li; Hui Zhou; Yan-guo Zhang (Biomass and Bioenergy, 2026)

Design of BDS-3 signal distortion bias model and analysis of its performance - Saisai Gao; Ran Li; Jiatong Wu; Xiaoyun Wan; Rui Guo; Xiaojie Li; Shanshi Zhou; Guang Yang (Advances in Space Research, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Spatial and seasonal variation in bioturbation potential of Macrobenthic communities in Bohai Bay - Yifeng Shi; Wenzhe Xu; Rui Gu; Wenxin Zhou; Guicheng Zhang; Yu Guo; Yiyan Guo; Jun Sun (Progress in Oceanography, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Depth-dependent effects of vegetation restoration on soil quality in ion-adsorbed rare earth leach residues: Insights from soil functions - Heng Zhang; Xianzhen Luo; Rui Zhang; Li Zhou; Rufeng Guo; Yuanwen Kuang; Dazhi Wen; Biao Qiu; Lingling Zhang (CATENA, 2026)

Echinacoside Improves Memory Function and Bone Mineral Density in the Aged SAMP8 Mouse Model - Rong Zhou; Ge Tian; Jing Yu; Rui Wang; Ning Peng; Xingzhi Guo; Rui Li (Molecular Neurobiology, 2026)

Per- and polyfluoroalkyl substances in China’s wastewater, surface water, and groundwater: occurrence characteristics, spatiotemporal distribution, and risk assessment - Qinru Wang; Rui Qiu; Yang Chen; Youqi Tao; Qi Zhou; Hongguang Guo (Environmental Geochemistry and Health, 2026)

Strategic sampling for training a semantic segmentation model in operational mapping: Case studies on cropland parcel extraction - Rui Lu; Ronghua Liao; Ran Meng; Yingchu Hu; Yi Zhao; Yan Guo; Yingfan Zhang; Zhou Shi; Su Ye (Remote Sensing of Environment, 2025)

Deciphering the core microbiomes and associated genes and metabolites during the Shanxi aged vinegar making process - Rui Ma; Mingxia Cheng; Qiong Zhou; Xiaojie Nan; Min Zhu; Shang Guo; Zhibin Zhang; Fang Gao; Jingang Gu (Food Bioscience, 2025)

Retraction notice to “A bioactive dextran-based hydrogel promote the healing of infected wounds via antibacterial and immunomodulatory” [Carbohydrate Polymers 291 (2022) 119558] - Lisheng Zhou; Liming Zhou; Chengxiu Wei; Rui Guo (Carbohydrate Polymers, 2025)

Sediment amplifies organic matter cycling and nutrients feedback in eutrophic lake zones - Junfeng Xing; Yuping Zhou; Ding He; Fen Guo; Penghui Li; Yuan Zhang; Rui Lv; Runze Xue; Changqing Liu; Yihua Xiao (Water Research, 2025)

Insights into the key odorants in Chimonanthus praecox var. concolor Mak. Flower using the sensomics approach - Peng Guo; Wei Guan; Runhu Xin; Yuanhao Zhou; Miao Liang; Yajian Wu; Rui Wang; Yuping Liu (Food Chemistry, 2025)

Enhanced effects of species richness on cadmium phytoextraction across eastern China: A meta-analysis - Rufeng Guo; Xianzhen Luo; Li Zhou; Rui Zhang; Lingling Zhang; Yuanwen Kuang; Biao Qiu; Dazhi Wen (Environmental Research, 2025)

Core microbiota with antimonite oxidation coupled nitrogen fixation traits persist in the rhizosphere of pioneer plants in antimony tailings - Hanbing Gao; Zhaohui Guo; Fenglian Huang; Shikai Li; Xiao He; Jaovola Ulrich Fernio; Wei lv; Ling Zhou; Shuyang Du; Min Shen; Rui Xu (Environmental Research, 2025)

The synergistic effect of triazine-N and secondary amine-N anchors iodine species with MXene composite cathode for stable aqueous Zn–I2 battery - Jing Ma; Yaoyao Linghu; Kai Yuan; Rui Zhou; Hui Gao; Peihua Zhao; Shaohui Guo; Huiqi Wang; Yongping Qu; Chao Shen; Keyu Xie (Chemical Engineering Journal, 2025)

Metagenomic insights into the synergistic properties and mechanisms of sludge microbial communities degrading polystyrene and polypropylene - Ying Zhou; Wei-hua Gu; Jian-feng Bai; Rui-xue Wang; Cheng-long Zhang; Yao-guang Guo; Cong Lu; Shan-ping Chen (Journal of Hazardous Materials, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Electrocatalytic removal of nitrate by non-noble Fe3C/Cu: Property, mechanism, and practical water treatment performance - Yang Guo; Hao Chen; Houfen Li; Jiming Liu; Xiao Zhang; Aijuan Zhou; Xiuping Yue; Rui Li; Jindong Wang; Pengxiao Liu; Hongtao Yu; Xu Zhao (Journal of Hazardous Materials, 2025)

Predicting estrogen receptor agonists from plastic additives across various aquatic-related species using machine learning and AlphaFold2 - Wen-Jun Shi; Zhou Cao; Xiao-Bing Long; Chong-Rui Yao; Jin-Ge Zhang; Chang-Er Chen; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Multifunctional Janus hydrogel targeting mitochondrial regulation and inflammatory pathways promotes infected burn wound repair - Xiaohui Li; Longbao Feng; Honglin Wu; Hao Yang; Peng Wang; Yongfei Chen; Yuxi Zhou; Jiayuan Zhu; Wei Xue; Rui Guo; Zhicheng Hu (Chemical Engineering Journal, 2025)

An automatic landmarking algorithm for leaf morphology based on conformal mapping - Peige Zhong; Xiaojun Liu; Yulu Ye; Rui Zhang; Hu Zhou; Yan Guo; Baoguo Li; Jinyu Zhu; Yuntao Ma (Computers and Electronics in Agriculture, 2025)

An oral recombinant human type 5 adenovirus vector vaccine encoding the S protein of Type I feline coronavirus effectively protection against FCoV challenge in cats - Gu-nan Deng; Chang-zhan Xie; Ke-lei Zhou; Chun-sai He; Yuan-Zhen Ma; A.-jia Ake; Rui Guo; Kai Li; Chen Peng; Bin Zhang (Veterinary Microbiology, 2025)

Traffic-based resilience assessment on urban road tunnel affected by fire accident - Rui Zhu; Dong-Mei Zhang; Zhong-Kai Huang; Xiao-yang Guo; Bin-lin Gan; Wen-ding Zhou (Tunnelling and Underground Space Technology, 2025)

Synergistic Pd-CoFe sites for efficient and selective electrooxidation of glycerol to glyceric acid coupled with H2 evolution - Jingtao Zhou; Jiu Chen; Rui Shi; Qiang Gao; Xin Zhao; Chuan-Jun Wang; Zhengxiao Guo; Edmund C.M. Tse; Fulai Liu; Yong Chen (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Identification of antifungal metabolites from a soil-derived Streptomyces strain active against Fusarium graminearum using genome mining - Xingyu Liu; Lubna Rahman; Yang Zhang; Rui Guo; Min Zhang; Wei Zhou (Biotechnology Letters, 2025)

Influence of geogrid reinforcement on the cracking characteristics of expansive soils: A laboratory study - Rui Zhang; Yu Zhou; Yipeng Guo; JianLong Zheng; Yufan Deng; Tian Lan (Geotextiles and Geomembranes, 2025)

Impacts of forest expansion on microbial diversity and community assembly in fragmented mountain ecosystems - Wen-Hui Lian; Wen-Sheng Zhao; Jia-Rui Han; Chao-Jian Hu; Guo-Yuan Shi; Fang Chen; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Mukhtiar Ali; Lei Dong; Ting Zhou; et al. (Environmental Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Subsurface drip irrigation with micro-nano bubble hydrogen water improves the salt tolerance of lettuce by regulating the antioxidant system and soil bacterial community - Jian Wang; Xin Guo; Qihang Zhao; Rui Chen; Guanlin Li; Bo Zhou; Pengfei Cheng (Applied Soil Ecology, 2025)

Monitoring nutrient and beneficial elements in the topsoil: the function of weathered background and later surficial process on their distribution - Bo Zhang; Kai-Ning Lv; Huan Li; Qin-Rui Zhang; Zhi-Qiang Yin; Wei-Zhi Zhou; Guo-Li Yuan (Environmental Monitoring and Assessment, 2025)

Corrigendum to “Differentiation of sow and mouse ovarian granulosa cells exposed to zearalenone in vitro using RNA-seq gene expression” [Toxicology and Applied Pharmacology, 350 (2018) 78–90] - Guo-Liang Zhang; Jun-Lin Song; Yi Zhou; Rui-Qian Zhang; Shun-Feng Cheng; Xiao-Feng Sun; Guo-Qing Qin; Wei Shen; Lan Li (Toxicology and Applied Pharmacology, 2025)

Borides and sulfide quantum dots co-enhanced the electrochemical property of metal organic framework/Ni3S2 composites for high-performance supercapacitors - Shuai Wu; Debin Cai; Hong Wang; Rui Zhou; Li Guo; Yanzhong Wang (Fuel, 2025)

Novel time-resolved fluorescent-based multiplex immunochromatography test strip for simultaneous detection of pesticides in vegetables - Zhengtao Li; Haowei Dong; Haifang Wang; Donghan Li; Shuxian Zhou; Shengxi Zhai; Jingcheng Huang; Rui Xu; Wenping Zhao; Mohamed Bedair M. Ahmed; Gili Bisker; Xia Sun; et al. (Food Chemistry, 2025)

Recent Advances in Machine Learning-Enhanced Joint Inversion of Seismic and Electromagnetic Data - Jixiao Ma; Yangfan Deng; Xin Li; Rui Guo; Hongyu Zhou; Maokun Li (Surveys in Geophysics, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Assaying the microbial features in rhizosphere of Panax quinquefolium L. under plant-derived smoke water based on metagenomic sequencing - Wanying Duan; Xiaoli Chen; Rui Li; Zhifang Ran; Lei Fang; Lanping Guo; Jie Zhou (Applied Soil Ecology, 2025)

TDCPP promotes apoptosis and inhibits the calcium signaling pathway in human neural stem cells - Ming-Rui Li; Guo-Rui Zhou; Zi-Ye Wang; Bo-Yang Li; Shu-Hui Men; Zhen-Guang Yan (Science of The Total Environment, 2025)

Susceptibility assessment of glacier-related debris flow on the southeastern Tibetan Plateau using different hybrid machine learning models - Rui Yu; Rui Guo; Liming Jiang; Yi Shao; Zhiwei Zhou (Science of The Total Environment, 2024)

Holocene paleoenvironment of the Nihewan Basin, China, inferred from high-resolution luminescence dating and a multiproxy analysis of gully sediments - Qing-Hao Ma; Yu-Jie Guo; Hua-Rui Lei; Yu-He Shen; Jia-Jing Wang; Ya Liu; Zhen-Yu Zhou; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Deciphering the biodegradation mechanism of 3,6-dichlorocarbazole using a novel isolate for its implication in bioaugmentation - Mi Feng; Rui Zhou; Zhaolong Zhu; Yantian Xie; Minghan Zhu; Zhanyu Guo; Xinghui Feng; Dongxia Fu; Jianhua Chen; Yanhong Du; Yao Huang (Chemical Engineering Journal, 2024)

Deciphering the nonlinear and synergistic role of building energy variables in shaping carbon emissions: A LightGBM- SHAP framework in office buildings - Congyue Zhou; Zhu Wang; Xuanli Wang; Rui Guo; Zhao Zhang; Xingwei Xiang; Yiqun Wu (Building and Environment, 2024)

EGR1 transcriptionally regulates SVEP1 to promote proliferation and migration in human coronary artery smooth muscle cells - Qiang Tian; Jia-He Chen; Yi Ding; Xin-Yu Wang; Jia-Yun Qiu; Qian Cao; Li-Li Zhuang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2024)

Comprehensive compositional analysis of liquid organic product prepared by industrialized hydrothermal cracking of biomass waste and its potential application as fertilizer - Rui Xia; Jue Wang; Xiao-xiao Yang; Qing-hai Li; Hui Zhou; Hui Sun; Yan-guo Zhang (Science of The Total Environment, 2024)

Assessment of seabed trench formation based on marine sediment properties and chain-bar penetration tests - Shengjie Rui; Hans Petter Jostad; Zefeng Zhou; Lizhong Wang; Svein Sævik; Yufei Wang; Zhen Guo (Engineering Geology, 2024)

Exploring the anti-gastric cancer mechanism of action of Bidentis Bipinnatae Herba based on network pharmacology, molecular docking, and cellular experimental validation - Linglong Guo; Yuyi Zhou; Rui Ma (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

Dexmedetomidine attenuates ferroptosis by Keap1-Nrf2/HO-1 pathway in LPS-induced acute kidney injury - Rui-Rui Luo; Jing Yang; Yan-Lin Sun; Bi-Ying Zhou; Si-Xuan Zhou; Guo-Xing Zhang; Ai-Xiang Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Semi-liquid metal-based highly permeable and adhesive electronic skin inspired by spider web - Rui Guo; Xiaoqing Li; Yingtong Zhou; Yuqi Zhang; Chengjie Jiang; Yang Yu; Qingting Tan; Wenbo Ding; Hongzhang Wang (Science Bulletin, 2024)

Research progress of natural polysaccharide-based and natural protein-based hydrogels for bacteria-infected wound healing - Huiqing Xu; Yilin Che; Rui Zhou; Lu Wang; Jiaying Huang; Wei Kong; Chang Liu; Lei Guo; Yixin Tang; Xue Wang; Xi Yang; Erlei Wang; et al. (Chemical Engineering Journal, 2024)

How territorial function determines CO2 emissions in China: An approach of spatial dimension - Jie Fan; Zheng Wang; Daojing Zhou; Rui Guo; Dong Chen; Baoyin Liu; Hanchu Liu; Qin Qiao; Jianxiong Wu (Journal of Geographical Sciences, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Wogonin preconditioning of MSCs improved their therapeutic efficiency for colitis through promoting glycolysis - Mengye Wu; Cuiping Li; Xue Zhou; Zhiyong Wu; Jianqi Feng; Xiaolu Guo; Rui Fang; Qinghai Lian; Ming Pan; Xiaorong Lai; Yanwen Peng (Inflammopharmacology, 2024)

Micronutrient perspective on COVID-19: Umbrella review and reanalysis of meta-analyses - Yafei Xie; Jianguo Xu; Dan Zhou; Mingyue Guo; Mengxiang Zhang; Ya Gao; Ming Liu; Jiyuan Shi; Kelu Yang; Qingyong Zheng; Liang Zhao; Yu Qin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Quercetin regulates dendritic cell activation by targeting STAT4 in the treatment of experimental autoimmune encephalomyelitis - Fang Zhou; Yu-Xin Guo; Rui Gao; Xiao-Yu Ji; Yu-Xuan Tang; Li-Bin Wang; Yuan Zhang; Xing Li (Toxicology and Applied Pharmacology, 2024)

SPAN secondary particles enabled high energy density Lithium-Sulfur battery - Weijing Zuo; Rui Li; Xiangkun Wu; Yawei Guo; Shoubin Zhou; Bohua Wen; Jiayan Luo; Lan Zhang (Chemical Engineering Journal, 2024)

Editorial: Frontiers in marine sciences, social sciences and engineering research related to marine (renewable) energy development - Shengjie Rui; Zhen Guo; Zefeng Zhou; Zhenkui Wang; Guanqiong Ye; Dongfang Ma (Frontiers in Marine Science, 2024)

Electrochemically assisted preparation of graphitic carbon nitride nanosheet membranes for efficient water purification - Yisa Zhou; Ya Zhang; Jian Xue; Rui Wang; Jiale Dong; Zongjie Yin; Chen Guo; Haihui Wang (Chemical Engineering Journal, 2024)

Soil moisture drives the shift from selection to complementarity effect in the rainfed maize/faba bean intercropping system - Wei Wang; Meng-Ying Li; Wei Zhang; Aziz Khan; Rui Zhou; Shuang-Guo Zhu; Bao-Zhong Wang; Yu-Miao Yang; Hong-Yan Tao; Wen-Bo Li; You-Cai Xiong (Plant and Soil, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Effect of nano-SiO2 modification on the seismic performance of recycled aggregate concrete shear walls - Yingwu Zhou; Liu Fan; Feng Xing; Wenwei Lin; Rui Hu; Menghuan Guo; Zhongfeng Zhu (Engineering Structures, 2024)

Impact of remaining roots on soil nematode communities in an aboveground plant functional group removal experiment - Yong Zheng; Ligai Huang; Xue Jiang; Rui Guo; Wenjie Wan; Luping Ye; Tibor A. Drost; Xianhui Zhou; Hui Guo; Juan Zuo; Peng Wang (Plant and Soil, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Retarding ice recrystallization by tamarind seed polysaccharide: Investigation in ice cream mixes and insights from molecular dynamics simulation - Xianbao Sun; Rui Guo; Taijie Zhan; Yuxing Kou; Xuan Ma; Hong Song; Wei Zhou; Lihua Song; Hui Zhang; Fan Xie; Chunmei Yuan; Zibo Song; et al. (Food Hydrocolloids, 2024)

Comprehensive evaluation of newly cultivated land sustainable utilization at project scale: A case study in Guangdong, China - Chang Guo; Xiaobin Jin; Xuhong Yang; Weiyi Xu; Rui Sun; Yinkang Zhou (Journal of Geographical Sciences, 2024)

Microplastics affect mosquito from aquatic to terrestrial lifestyles and are transferred to mammals through mosquito bites - Jian-hang Li; Xiao-hui Liu; Guo-rui Liang; He-ting Gao; Si-han Guo; Xin-yu Zhou; Dan Xing; Teng Zhao; Chun-xiao Li (Science of The Total Environment, 2024)

Biochar reduces the cadmium content of Panax quinquefolium L. by improving rhizosphere microecology - Xiaoli Chen; Zhifang Ran; Rui Li; Wanying Duan; Zhengjian Song; Lei Fang; Lanping Guo; Jie Zhou (Science of The Total Environment, 2024)

TDA/rGO@WS with Joule heat and photothermal synergistic effect: A promising adsorption material for all–weather recovery of viscous oil spills at sea - Min Du; Haokun Shi; Rui Yin; Jianlei Yang; Fulin Shi; Qinggong Zheng; Yu Zhou; Ruixue Guo; Wanqing Wu (Journal of Hazardous Materials, 2024)

Removing refractory organic substances from landfill leachate using a nanofiltration membrane bioreactor: Performance and mechanisms - Chu Zhou; Na Li; Wenbin Guo; Rui Wang; Yaohua Yan; Senlin Shao (Chemical Engineering Journal, 2024)

Water Properties and Diffusive Convection in the Canada Basin - Ling Qu; Shuangxi Guo; Shengqi Zhou; Yuanzheng Lu; Mingquan Zhu; Xianrong Cen; Di Li; Wei Zhou; Tao Xu; Miao Sun; Rui Zeng (Journal of Marine Science and Engineering, 2024)
The aim of this study is to better understand diffusive convection (DC) and its role in the upper ocean dynamic environment and sea ice melting in the Canada Basin. Based on a moored dataset with 6737 profiles collected from August 2003 to August 2011 in the upper layer of the Canada Basin, DC between the warm and salty Atlantic Water (AW) and the colder and less salty Lower Halocline Water (LHW) were investigated. The moorings were designated at four stations: A, B, C, and D, located at the southwestern, southeastern, northeastern, and northwestern parts of the basin, respectively. During the observation period, the temperature, salinity, and depth of the AW and LHW exhibited unique temporal variations. The temperature and salinity of the AW varied among stations, with a decreasing trend from northwest to southeast, consistent with the propagation path of the AW in the Canada Basin. The temperature and salinity of the LHW were similar at all stations. The AW and LHW cores were located between depths of 320–500 m and 160–300 m, respectively, and both gradually deepened over time. Distinct DC staircase structures were observed between the AW and LHW, more pronounced at stations C and D than at stations A and B, which is speculated to be related to eddies at stations A and B during the observation period. The vertical heat fluxes through the DC staircase layer at stations C and D (FHc_C and FHc_D) were estimated using an empirical formula. FHc_C ranged from 0.05 to 0.94 W/m2, and FHc_D ranged from 0.05 to 0.6 W/m2, with the maximum probability value for both at approximately 0.2 W/m2. The effective diffusivities at these two stations (KT_C and KT_D) are similar, ranging from 2 × 10−6 to 3 × 10−5 m2/s, with the highest probability occurring at 6 × 10−6 m2/s. Both the probability density function of the heat flux and the effective diffusivity skewed towards larger values and obey a lognormal distribution, indicating turbulence intermittency of the DC staircase in the Canada Basin. These finding offers new insights into the heat transport and turbulence in the DC staircase, and then bring a deeper understanding of sea ice melting in the Canada Basin.

Spatial distribution characteristics of perfluoroalkyl substances in bulk and grain size fractionated sediments in Shenzhen Bay - Haoshuai Li; Zimin Wang; Yang Zhou; Cui Shi; Huayang Gan; Fang Chen; Lei Xing; Danxu Guo; Longhai Zhu; Nan Wang; Shuhong Fang; Rui Bao (Marine Pollution Bulletin, 2024)

The application of human-derived cell lines in neurotoxicity studies of environmental pollutants - Ming-Rui Li; Shu-Hui Men; Zi-Ye Wang; Chen Liu; Guo-Rui Zhou; Zhen-Guang Yan (Science of The Total Environment, 2024)

Thallium content in vegetables and derivation of threshold for safe food production in soil: A meta-analysis - Xiyuan Xiao; Wenqiang Zhou; Zhaohui Guo; Chi Peng; Rui Xu; Yunxia Zhang; Yunyun Yang (Science of The Total Environment, 2024)

A tale of two vein types: Bed-parallel fibrous versus blocky filled fractures in organic-rich shales and their overpressured hydrocarbon fluids - Miao Wang; Feng Liang; Tong Lin; Yelei Wang; Hui Zhang; Qian Huang; Yifan Song; Tingting Liu; Yanwei Feng; Rui Ni; Xiaoying Guo; Tengfei Zhou; et al. (Marine and Petroleum Geology, 2024)

Integrating bulk-RNA sequencing and single-cell sequencing analyses to characterize adenosine-enriched tumor microenvironment landscape and develop an adenosine-related prognostic signature predicting immunotherapy in lung adenocarcinoma - Tao Han; Jing Wu; Yafeng Liu; Jiawei Zhou; Rui Miao; Jianqiang Guo; Zhi Xu; Yingru Xing; Ying Bai; Dong Hu (Functional & Integrative Genomics, 2024)

Emission characteristics of intermediate volatility organic compounds from a Chinese gasoline engine under varied operating conditions: Influence of fuel, velocity, torque, rotational speed, and after-treatment device - Rongzhi Tang; Song Guo; Kai Song; Ying Yu; Rui Tan; Hui Wang; Kefan Liu; Ruizhe Shen; Shiyi Chen; Limin Zeng; Zhou Zhang; Wenbin Zhang; et al. (Science of The Total Environment, 2024)

The Protective Effect of Chronic Intermittent Hypobaric Hypoxia on Preventing the Destruction of CD34+ Haematopoietic Stem Cells in Aplastic Anaemia by Modulating the Th1/Th2 Balance - Hui Guo; Yilin Zhao; Rui Mu; Guangdao Zhang; Shuxian Chen; Xinwei Cao; Kangcan Liu; Yiran Liu; Baiyun Dai; Yuan Zhou; Chuan Wang; Jing Yang (Stem Cell Reviews and Reports, 2024)

AM fungus promotes wheat grain filling via improving rhizospheric water & nutrient availability under drought and low density - Hai-Xia Duan; Chong-Liang Luo; Rui Zhou; Ling Zhao; Shuang-Guo Zhu; Yinglong Chen; Ying Zhu; You-Cai Xiong (Applied Soil Ecology, 2024)

Preparation of microstructure controllable Al/WO3/F2603 MICs by droplet microfluidic technology to improve combustion performance - Jinqiang Zhou; Qi Pan; Xueyong Guo; Jianxin Nie; Rui Liu (Chemical Engineering Journal, 2023)

Single-cell transcriptome analysis revealing the intratumoral heterogeneity of ccRCC and validation of MT2A in pathogenesis - Jie Wang; Zili Zuo; Zongze Yu; Zhigui Chen; Xiangdi Meng; Zhaosen Ma; Jiqiang Niu; Rui Guo; Lisa Jia Tran; Jing Zhang; Tianxiao Jiang; Fangdie Ye; et al. (Functional & Integrative Genomics, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

What is affecting the improvement of green innovation efficiency in the old industrial base: evidence from Northeast China - Fuyou Guo; Mingxi Zhou; Ligeer De; Rui Li; Yu Zhang (Environmental Science and Pollution Research, 2023)

Gravity-driven membrane system treating heavy metals-containing secondary effluent: Improved removal of heavy metals and mechanism - Xiaobin Ma; Yanrui Wang; Le Tong; Jiaoying Luo; Rui Chen; Yuanxin Wang; Xishou Guo; Jinlong Wang; Zhiwei Zhou; Jingyao Qi; Guibai Li; Heng Liang; et al. (Chemosphere, 2023)

Soil phosphorus availability mediates facilitation dynamic in maize-grass pea intercropping system - Shuang-Guo Zhu; Wesly Kiprotich; Zheng-Guo Cheng; Rui Zhou; Jing-Wei Fan; Hao Zhu; Wen-Ying Wang; Wei Wang; Ren-Qing Wang; Hong-Yan Tao; You-Cai Xiong (Soil and Tillage Research, 2023)

Effects of interspecific interactions on soil carbon emission and efficiency in the semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Shuang-Guo Zhu; Hong-Yan Tao; Aziz Khan; Aimee Grace Uzamurera; Bao-Zhong Wang; Jun-Ming Jin; Yue Ma; Wen-Bo Li; Xiu-Ping Tao; et al. (Soil and Tillage Research, 2023)

Effect of Triton X-100 on Shiraia laccase production and its application in triclosan biodegradation - Rui Peng Cong; Yan Hua Guo; Jian Qin Zhou; Jian Wen Wang (Sustainable Chemistry and Pharmacy, 2023)

Rapid determination of the relative configuration of diverse 8,4′-oxyneolignans by NMR analysis: Retrospective studies, improvement and structural revision - Peng Zhao; Li-Li Lou; Ben-Song Xin; Zhi-Yuan Li; Rui Guo; Wei-Yu Zhou; Tian-Ming Lv; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

Seismic and hydrological triggers for a complex cascading geohazard of the Tianmo Gully in the southeastern Tibetan Plateau - Rui Guo; Liming Jiang; Zhida Xu; Chao Li; Ronggang Huang; Zhiwei Zhou; Tao Li; Yi Liu; Hansheng Wang; Xuanmei Fan (Engineering Geology, 2023)

Temporal variation of per- and polyfluoroalkyl substances (PFASs) abundances in Shenzhen Bay sediments over past 65 years - Danxu Guo; Yang Zhou; Fang Chen; Zimin Wang; Haoshuai Li; Nan Wang; Huayang Gan; Shuhong Fang; Rui Bao (Marine Pollution Bulletin, 2023)

Antimicrobial hydrogel microneedle loading verteporfin promotes skin regeneration by blocking mechanotransduction signaling - Chengxiu Wei; Chuangang You; Liming Zhou; Huiling Liu; Shihao Zhou; Xingang Wang; Rui Guo (Chemical Engineering Journal, 2023)

Star-like, dopant-free, corannulene-cored hole transporting materials for efficient inverted perovskite solar cells - Ming-Wei An; Bolin Li; Bin-Wen Chen; Zuo-Chang Chen; Han-Rui Tian; Lin-Long Deng; Xugang Guo; Zhou Xing (Chemical Engineering Journal, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Centimeter-level clock synchronization and space-borne timescale generation for BDS-3 using inter-satellite link measurements - Jianhua Yang; Chengpan Tang; Xiaogong Hu; Shanshi Zhou; Li Liu; Yezhi Song; Yufei Yang; Rui Guo; Shuai Liu; Junyang Pan (Journal of Geodesy, 2023)

Nanostructured carboxylated-wood aerogel membrane for high-efficiency removal of Cu (II) ions from wastewater - Wen He; Jizhou Cao; Feiyu Guo; Zhihao Guo; Peiguo Zhou; Rui Wang; Shuang Liang; Qunyan Pang; Bairen Wei; Yue Jiao; Tripti Singh; Qiliang Fu (Chemical Engineering Journal, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Short- and medium-chain chlorinated paraffins in urban road dust of Shanghai, China: concentrations, source apportionment and human exposure assessment - Xue-Tong Wang; Cheng-Lin Wang; Ying Zhou; Guo-Fa Ren; Rui Fu; Jing An (Environmental Geochemistry and Health, 2023)

Engineering triple internal electric fields in Ag NWs@BaTiO3 composites for ultrasonic-visible-light driven antibacterial activity - Guoqiang Shu; Yaqi Lin; Rui Zhong; Xiaofan Su; Shanhong Guo; Chao Wang; Changan Zhou; Lei Song; Li Xie; Kui Ma; Hairong Yue (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A corrected p-y curve model for large-diameter pile foundation of offshore wind turbine - Xiao-ling Zhang; Rui Zhou; Guo-liang Zhang; Yan Han (Ocean Engineering, 2023)

Efficient removal of Cr(VI) by the modified biochar with chitosan schiff base and MnFe2O4 nanoparticles: Adsorption and mechanism analysis - Ling Yan; Weijuan Guo; Binbin Huang; Yujun Chen; Xinyu Ren; Yiyang Shen; Yefeng Zhou; Rui Cheng; Jie Zhang; Muqing Qiu; Baowei Hu (Journal of Environmental Chemical Engineering, 2023)

Quantify the effect of manure fertilizer addition and optimal nitrogen input on rainfed wheat yield and nitrogen requirement using nitrogen nutrition index - Pengzhao Liu; Xingyu Guo; Dong Zhou; Qi Zhang; Xiaolong Ren; Rui Wang; Xiaoli Wang; Xiaoli Chen; Jun Li (Agriculture, Ecosystems & Environment, 2023)

Pregnancy and lactation mixed exposure to lead, cadmium, and mercury alters maternal-offspring single heavy metal load: A factorial design - Guihua Du; Fankun Zhou; Lu Ouyang; Kai Wang; Shaoqi Rao; Rui Su; Yanhui Zhu; Kechu Guo; Jinmei Xiao; Jie Xie; Qi Li; Chang Feng; et al. (International Journal of Hygiene and Environmental Health, 2023)

Interaction of permafrost degradation and thermokarst lakes in the Qinghai–Tibet Plateau - Zhida Xu; Liming Jiang; Rui Guo; Ronggang Huang; Zhiwei Zhou; Fujun Niu; Zhiping Jiao (Geomorphology, 2023)

Fabricated noble-metal free Co2B/g-C3N4 photocatalyst with 2D/2D structure achieved remarkable water splitting performance from visible to near-infrared wavelengths - Jun-ying Tang; Rui-tang Guo; Wei-guo Pan; Wei-guo Zhou (Fuel, 2023)

Territorial function differentiation and its comprehensive regionalization in China - Jie Fan; Kan Zhou; Kerong Sheng; Rui Guo; Dong Chen; Yafei Wang; Hanchu Liu; Zheng Wang; Yong Sun; Jie Zhang; Jianxiong Wu; Hao Zhao (Science China Earth Sciences, 2023)

Intercrop overyielding weakened by high inputs: Global meta-analysis with experimental validation - Shuang-Guo Zhu; Hao Zhu; Rui Zhou; Wei Zhang; Wei Wang; Yi-Ning Zhou; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; Hong-Yan Tao; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Selective detection of trace carbon monoxide at room temperature based on CuO nanosheets exposed to (111) crystal facets - Yuanyuan Wu; Ji Li; Mingsong Lv; Xianfa Zhang; Rui Gao; Chuanyu Guo; Xiaoli Cheng; Xin Zhou; Yingming Xu; Shan Gao; Zoltán Major; Lihua Huo (Journal of Hazardous Materials, 2023)

Controlled design of Na–P1 zeolite/ porous carbon composites from coal gasification fine slag for high-performance adsorbent - Rui Shu; Qixia Qiao; Feiqiang Guo; Kaiming Dong; Sha Liu; Liya Xu; Yonghui Bai; Nan Zhou (Environmental Research, 2023)

A High-efficiency blue-LED-excitable NIR-II-emitting MgO:Cr3+,Ni2+ phosphor for future broadband light source toward multifunctional NIR spectroscopy applications - Bo-Mei Liu; Xiao-Xuan Guo; Lu-Yu Cao; Lin Huang; Rui Zou; Zhi Zhou; Jing Wang (Chemical Engineering Journal, 2023)

Soil water and phosphorus availability determines plant-plant facilitation in maize-grass pea intercropping system - Shuang-Guo Zhu; Hao Zhu; Zheng-Guo Cheng; Rui Zhou; Yu-Miao Yang; Jing Wang; Wei Wang; Bao-Zhong Wang; Hong-Yan Tao; You-Cai Xiong (Plant and Soil, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Xanthophyll cycle-related non-photochemical quenching protects Sargassum thunbergii from high light-induced photoinhibition - Guo-Ning Nan; Xiao-Qun Zhou; Xiu-Mei Zhang; Quan-Sheng Zhang; Zi-Min Hu; Rui-Ping Huang; Di Zhang (Frontiers in Marine Science, 2022)
As a common macroalga living in the intertidal zone, Sargassum thunbergii (Sargassaceae, Phaeophyta) is often exposed to drastic changes in solar photosynthetically active radiation during a diurnal cycle; thus, the potential photosynthetic adaptation processes deserve attention. In this work, we examined the photosynthetic performance and xanthophyll cycle activity of this alga in response to high light (1,200 μmol photons m –2 s –1 , the average in-situ light intensity at noon) by using chlorophyll fluorescence and high-performance liquid chromatography (HPLC). On exposure to high light, a rapid decrease in the effective quantum yield of photosystem II (PSII) (Y(II)) occurred, indicating down-regulation of PSII activity; a corresponding increase in non-photochemical quenching (NPQ) indicated the existence of energy-dissipating cycles. After turning off the light, Y(II) gradually increased to 0.7, accompanied by a decrease in NPQ. However, no complete recovery of NPQ was observed, and its value remained at ≈4, even after an 80-min dark treatment. The size of the xanthophyll cycle pigments pool was quantified using HPLC and was found to be ≈16 mol mol −1 Chl a × 100. The activity of the xanthophyll cycle, characterized by a de-epoxidation state (DPS), could reach up to ≈0.5. Such a large pigments pool and rapid accumulation of zeaxanthin may allow S. thunbergii to induce high values of NPQ (≈10). These results were further complemented by inhibitor (dithiothreitol, DTT) and pre-illumination experiments showing that (1) both NPQ and the xanthophyll cycle could be inhibited by DTT, and there was always a strong positive correlation between NPQ and DPS; (2) the previously formed antheraxanthin exhibited a long retention time and a slow epoxidation; and (3) the long retention of antheraxanthin contributed to a rapid accumulation of zeaxanthin. In conclusion, our present study demonstrated that xanthophyll cycle-induced NPQ can significantly protect S. thunbergii from light fluctuations in the intertidal zone.

Modification of alternative splicing in bovine somatic cell nuclear transfer embryos using engineered CRISPR-Cas13d - Rui Cheng; Xiaoman Zheng; Yingmei Wang; Xing Ma; Xin Liu; Wenjun Xu; Mengyun Wang; Yuanpeng Gao; Xupeng Xing; Chuan Zhou; Hongzheng Sun; Zekun Guo; et al. (Science China Life Sciences, 2022)

The structure and subduction relicts of the Changchun–Yanji suture, NE China: new evidence from deep seismic reflection profiling - Jiaduo Zhang; Hesheng Hou; Jianbo Zhou; Wei Fu; Rui Guo; Zongdong Pan; Hengcheng Ying (International Journal of Earth Sciences, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Effects of two Mn-based nanomaterials on soybean antioxidant system and mineral element homeostasis - Yaqi Jiang; Pingfan Zhou; Tengtao Ma; Muhammad Adeel; Noman Shakoor; Yuanbo Li; Mingshu Li; Manlin Guo; Yukui Rui (Environmental Science and Pollution Research, 2022)

Orbit determination, clock estimation and performance evaluation of BDS-3 PPP-B2b service - Chengpan Tang; Xiaogong Hu; Jinping Chen; Li Liu; Shanshi Zhou; Rui Guo; Xiaojie Li; Feng He; Jinhuo Liu; Jianhua Yang (Journal of Geodesy, 2022)

The functional evolution and system equilibrium of urban and rural territories - Jie Fan; Sisi Li; Zhongrui Sun; Rui Guo; Kan Zhou; Dong Chen; Jianxiong Wu (Journal of Geographical Sciences, 2022)

Effects of Biochar on the Growth, Ginsenoside Content, and Soil Microbial Community Composition of Panax quinquefolium L - Xiaotong Yang; Zhifang Ran; Rui Li; Lei Fang; Jie Zhou; Lanping Guo (Journal of Soil Science and Plant Nutrition, 2022)

TRIP13 knockdown inhibits the proliferation, migration, invasion, and promotes apoptosis by suppressing PI3K/AKT signaling pathway in U2OS cells - De-Chen Yu; Xiang-Yi Chen; Hai-Yu Zhou; De-Quan Yu; Xiao-Lei Yu; Yi-Cun Hu; Rui-Hao Zhang; Xiao-Bo Zhang; Kun Zhang; Mao-Qiang Lin; Xi-Dan Gao; Tao-Wen Guo (Molecular Biology Reports, 2022)

Numerical investigations on load transfer of mooring line considering chain–seabed dynamic interaction - Shengjie Rui; Zhen Guo; Lizhong Wang; Haochen Liu; Wenjie Zhou (Marine Georesources & Geotechnology, 2021)

Occurrence, source apportionment, and carcinogenic risk assessment of polycyclic aromatic hydrocarbons in urban road dusts in Shanghai - Xue-Tong Wang; Rui Fu; Ying Zhou; Cheng-Lin Wang; Guo-Fa Ren; Xiao-Li Wang; Hui Li (Environmental Science and Pollution Research, 2021)

Multistage geomorphic evolution of the Central Canyon in the Qiongdongnan Basin, NW South China Sea - Chao Li; Guojun Chen; Qianshan Zhou; Chengze Li; Rui Sun; Chengfu Lyu; Shuai Guo (Marine Geophysical Research, 2021)

Two new dihydroisocoumarins with antimicrobial activities from the fungus Penicillium sp. XR046 collected from Xinren coal area - Guo-Bo Xu; Fei-Yu Yang; Xin-Yu Wu; Rui Li; Meng Zhou; Bing Wang; Xiao-Sheng Yang; Ting-Ting Zhang; Shang-Gao Liao (Natural Product Research, 2021)

Microseismicity-based method for the dynamic estimation of the potential rockburst scale during tunnel excavation - Guo-Feng Liu; Quan Jiang; Guang-Liang Feng; Dong-Fang Chen; Bing-Rui Chen; Zhou-Neng Zhao (Bulletin of Engineering Geology and the Environment, 2021)

BeiDou-3 broadcast clock estimation by integration of observations of regional tracking stations and inter-satellite links - Yufei Yang; Yuanxi Yang; Xiaogong Hu; Chengpan Tang; Rui Guo; Zhanshi Zhou; Junyi Xu; Junyang Pan; Mudan Su (GPS Solutions, 2021)

Hydrogeochemical and isotopic characteristics of groundwater in Xinchang preselected site and their implications - Zhichao Zhou; Ju Wang; Rui Su; Yonghai Guo; Jingbo Zhao; Ming Zhang; Ruili Ji; Yanan Li; Jiebiao Li (Environmental Science and Pollution Research, 2020)

Evolution of Neolithic site distribution (9.0–4.0 ka BP) in Anhui, East China - Li Wu; Xiaoling Sun; Wei Sun; Cheng Zhu; Tongxin Zhu; Shuguang Lu; Hui Zhou; Qingchun Guo; Houchun Guan; Wei Xie; Rui Ke; Guiping Lin (Journal of Geographical Sciences, 2020)

α -Tetralone glycosides from the green walnut husks of Juglans mandshurica Maxim. and their cytotoxic activities - Yuan-Yuan Zhou; Shuang Guo; Ying Wang; Hong-Juan Song; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2020)

Integrated analysis of miRNAs and their targets reveals that miR319c/TCP2 regulates apical bud burst in tea plant (Camellia sinensis) - Shengrui Liu; Xiaozeng Mi; Ran Zhang; Yanlin An; Qiying Zhou; Tianyuan Yang; Xiaobo Xia; Rui Guo; Xuewen Wang; Chaoling Wei (Planta, 2019)

Two new sesquineolignans from the seeds of Crataegus pinnatifida and their β -amyloid aggregation inhibitory activitiy - Rui Guo; Le Zhou; Peng Zhao; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2019)

A new triterpene from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hong-Juan Song; Shuang Guo; Ying Wang; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2019)

Industrial environmental efficiency assessment for China’s western regions by using a SBM-based DEA - Si-Dai Guo; Hang Li; Rui Zhao; Xiao Zhou (Environmental Science and Pollution Research, 2019)

ANKRD49 inhibits etoposide-induced intrinsic apoptosis of GC-1 cells by modulating NF-κB signaling - Xia Zhou; Wen-tao Wang; Jia Sun; Hong-yan Liu; Xin-yan Bai; Juan-juan Liu; Bao-feng Yu; Rui Guo; Hai-long Wang (Molecular and Cellular Biochemistry, 2019)

Highly Sensitive and Selective Fluorescent Probe for Detection of Fe3+ Based on Rhodamine Fluorophore - Yang Wang; Rui Guo; Xufeng Hou; Mengmeng Lei; Qihang Zhou; Zhihong Xu (Journal of Fluorescence, 2019)

Numerical Simulations of Wave-Induced Soil Erosion in Silty Sand Seabeds - Zhen Guo; Wenjie Zhou; Congbo Zhu; Feng Yuan; Shengjie Rui (Journal of Marine Science and Engineering, 2019)
Silty sand is a kind of typical marine sediment that is widely distributed in the offshore areas of East China. It has been found that under continuous actions of wave pressure, a mass of fine particles will gradually rise up to the surface of silty sand seabeds, i.e., the phenomenon called wave-induced soil erosion. This is thought to be due to the seepage flow caused by the pore-pressure accumulation within the seabed. In this paper, a kind of three-phase soil model (soil skeleton, pore fluid, and fluidized soil particles) is established to simulate the process of wave-induced soil erosion. In the simulations, the analytical solution for wave-induced pore-pressure accumulation was used, and Darcy flow law, mass conservation, and generation equations were coupled. Then, the time characteristics of wave-induced soil erosion in the seabed were studied, especially for the effects of wave height, wave period, and critical concentration of fluidized particles. It can be concluded that the most significant soil erosion under wave actions appears at the shallow seabed. With the increases of wave height and critical concentration of fluidized particles, the soil erosion rate and erosion degree increase obviously, and there exists a particular wave period that will lead to the most severe and the fastest rate of soil erosion in the seabed.

Comparative detection of Karenia mikimotoi by exponential rolling circle amplification (E-RCA) and double-ligation E-RCA - Chunyun Zhang; Rui Sun; Yuanyuan Wang; Guofu Chen; Changlu Guo; Jin Zhou (Journal of Applied Phycology, 2019)

The IMPDH inhibitors, ribavirin and mycophenolic acid, inhibit peste des petits ruminants virus infection - Qiu-yan Chang; Fu-cheng Guo; Xue-rui Li; Jian-hua Zhou; Xuepeng Cai; Qiuwei Pan; Xiao-xia Ma (Veterinary Research Communications, 2018)

Genome-Wide Identification of Circular RNAs in Fungal Parasite Nosema ceranae - Rui Guo; Dafu Chen; Huazhi Chen; Cuiling Xiong; Yanzhen Zheng; Chunsheng Hou; Yu Du; Sihai Geng; Haipeng Wang; Zhou Dingding; Guo Yilong (Current Microbiology, 2018)

Initial results of centralized autonomous orbit determination of the new-generation BDS satellites with inter-satellite link measurements - Chengpan Tang; Xiaogong Hu; Shanshi Zhou; Li Liu; Junyang Pan; Liucheng Chen; Rui Guo; Lingfeng Zhu; Guangming Hu; Xiaojie Li; Feng He; Zhiqiao Chang (Journal of Geodesy, 2018)

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Effects of fine particle content and sample scale on the failure properties of loose landslide deposits - Bin-rui Gan; Xing-guo Yang; Ming-liang Chen; Jia-wen Zhou (Arabian Journal of Geosciences, 2018)

Correction to: Effects of Moisture-Induced Crystallization on the Aerosol Performance of Spray Dried Amorphous Ciprofloxacin Powder Formulations - Nivedita Shetty; Lingfei Zeng; Sharad Mangal; Haichen Nie; Matthew R. Rowles; Rui Guo; Youngwoo Han; Joon Hyeong Park; Qi Zhou (Pharmaceutical Research, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Physico-Chemical Properties, Aerosolization and Dissolution of Co-Spray Dried Azithromycin Particles with L-Leucine for Inhalation - Sharad Mangal; Haichen Nie; Rongkun Xu; Rui Guo; Alex Cavallaro; Dmitry Zemlyanov; Qi Zhou (Pharmaceutical Research, 2018)

Effects of Moisture-Induced Crystallization on the Aerosol Performance of Spray Dried Amorphous Ciprofloxacin Powder Formulations - Nivedita Shetty; Lingfei Zeng; Sharad Mangal; Haichen Nie; Matthew R. Rowles; Rui Guo; Youngwoo Han; Joon Hyeong Park; Qi Zhou (Pharmaceutical Research, 2018)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Warming Effects on Ecosystem Carbon Fluxes Are Modulated by Plant Functional Types - Ji Chen; Yiqi Luo; Jianyang Xia; Kevin R. Wilcox; Junji Cao; Xuhui Zhou; Lifen Jiang; Shuli Niu; Katerina Y. Estera; Rujin Huang; Feng Wu; Tafeng Hu; et al. (Ecosystems, 2017)

MicroRNA-9 Mediates the Cell Apoptosis by Targeting Bcl2l11 in Ischemic Stroke - Na Wei; Lin Xiao; Rui Xue; Dandan Zhang; Jun Zhou; Huayan Ren; Si Guo; Jingjing Xu (Molecular Neurobiology, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

The Roles of Genes in the Neuronal Migration and Neurite Outgrowth Network in Developmental Dyslexia: Single- and Multiple-Risk Genetic Variants - Shanshan Shao; Rui Kong; Li Zou; Rong Zhong; Jiao Lou; Jie Zhou; Shengnan Guo; Jia Wang; Xiaohui Zhang; Jiajia Zhang; Ranran Song (Molecular Neurobiology, 2016)

Cloning and characterizing of the murine IRF-3 gene promoter region - Hua-Guo Xu; Lifei Liu; Shan Gao; Rui Jin; Wei Ren; Guo-Ping Zhou (Immunologic Research, 2016)

Two new triterpenoid glycosides from the stems of Camellia oleifera Abel - Qing-Wei Yan; Hui-Zheng Fu; Yue-Hua Luo; Guo-Ping Zhou; Kai-Hua Wan; Rui-Jian Zhong (Natural Product Research, 2016)

Submerged macrophytes shape the abundance and diversity of bacterial denitrifiers in bacterioplankton and epiphyton in the Shallow Fresh Lake Taihu, China - Zhou Fan; Rui-ming Han; Jie Ma; Guo-xiang Wang (Environmental Science and Pollution Research, 2016)

ZmDBF3, a Novel Transcription Factor from Maize (Zea mays L.), Is Involved in Multiple Abiotic Stress Tolerance - Wei Zhou; Cheng-Guo Jia; Xian Wu; Rui-Xue Hu; Gang Yu; Xiang-Hui Zhang; Jin-Liang Liu; Hong-Yu Pan (Plant Molecular Biology Reporter, 2016)

Distribution of the Vrn-D1b allele associated with facultative growth habit in Chinese wheat accessions - Xian-rui Guo; Yuan-yuan Wang; Ling-zhi Meng; Hong-wei Liu; Li Yang; Yang Zhou; Hong-jun Zhang (Euphytica, 2015)

Meiothermus roseus sp. nov., a thermophilic bacterium isolated from a geothermal area - Hong Ming; Yan-Yan Duan; Qian-Qian Guo; Yi-Rui Yin; En-Min Zhou; Lan Liu; Shuai Li; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Baicalein inhibits prostate cancer cell growth and metastasis via the caveolin-1/AKT/mTOR pathway - Zhaoxin Guo; Xiaolin Hu; Zhaoquan Xing; Rui Xing; Renguang Lv; Xiangyu Cheng; Jing Su; Zunlin Zhou; Zhonghua Xu; Sten Nilsson; Zhaoxu Liu (Molecular and Cellular Biochemistry, 2015)

All-trans retinoic acid up-regulates the human CD2AP gene expression through Sp1/Sp3 binding sites - Hua-Guo Xu; Rui Jin; Shan Gao; Wei Ren; Li Zou; Lifei Liu; Guo-Ping Zhou (Immunologic Research, 2015)

Integrated SWAT model and statistical downscaling for estimating streamflow response to climate change in the Lake Dianchi watershed, China - Jing Zhou; Dan He; Yufeng Xie; Yong Liu; Yonghui Yang; Hu Sheng; Huaicheng Guo; Lei Zhao; Rui Zou (Stochastic Environmental Research and Risk Assessment, 2015)

PtAKT1 maintains selective absorption capacity for K+ over Na+ in halophyte Puccinellia tenuiflora under salt stress - Pei Wang; Qiang Guo; Qian Wang; Xiang-Rui Zhou; Suo-Min Wang (Acta Physiologiae Plantarum, 2015)

Heterologous expression and characterization of a novel halotolerant, thermostable, and alkali-stable GH6 endoglucanase from Thermobifida halotolerans - Yi-Rui Yin; Feng Zhang; Qing-Wen Hu; Wen-Dong Xian; Wael N. Hozzein; En-Min Zhou; Hong Ming; Guo-Xing Nie; Wen-Jun Li (Biotechnology Letters, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Phylogenetic relationships between Leymus and related diploid Triticeae species revealed by ISSR markers - Guo-Ye Guo; Rui-Wu Yang; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Fang Chen; Sheng-Hua Wang (Biologia, 2014)

Streptomyces calidiresistens sp. nov., isolated from a hot spring sediment - Yan-Yan Duan; Hong Ming; Lei Dong; Yi-Rui Yin; Yi Zhang; En-Min Zhou; Lan Liu; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Roseomonas alkaliterrae sp. nov., isolated from an alkali geothermal soil sample in Tengchong, Yunnan, south-west China - Lei Dong; Hong Ming; Yi-Rui Yin; Yan-Yan Duan; En-Min Zhou; Guo-Xing Nie; Hui-Geng Feng; Lan Liu; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Zhizhongheella caldifontis gen. nov., sp. nov., a novel member of the family Comamonadaceae - Lei Dong; Hong Ming; Lan Liu; En-Min Zhou; Yi-Rui Yin; Yan-Yan Duan; Guo-Xing Nie; Hui-Geng Feng; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

JNK Is Necessary for Oligodendrocyte Precursor Cell Proliferation Induced by the Conditioned Medium from B104 Neuroblastoma Cells - Jing-Xing Zhang; Yi-Fan Feng; Qi Qi; Lin Shen; Rui Wang; Jian-Sheng Zhou; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2014)

The apoptosis of peripheral blood lymphocytes promoted by hyperbaric oxygen treatment contributes to attenuate the severity of early stage acute pancreatitis in rats - Xuewei Bai; Zengfu Song; Yanmei Zhou; Shangha Pan; Feng Wang; Zuoming Guo; Maitao Jiang; Gang Wang; Rui Kong; Bei Sun (Apoptosis, 2014)

Characterization of microRNA expression profiles in 3T3-L1 adipocytes overexpressing C10orf116 - Jie Qiu; Xiao-guang Zhou; Xiao-yu Zhou; Chun Zhu; Chun-mei Shi; Chen-bo Ji; Rui Cheng; Yong Li; Xi-rong Guo (Molecular Biology Reports, 2013)

Vulcaniibacterium tengchongense gen. nov., sp. nov. isolated from a geothermally heated soil sample, and reclassification of Lysobacter thermophilus Wei et al. 2012 as Vulcaniibacterium thermophilum comb. nov. - Tian-Tian Yu; En-Min Zhou; Yi-Rui Yin; Ji-Cheng Yao; Hong Ming; Lei Dong; Shuai Li; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Molecular Cloning and Characterization of the PsbP Domain Protein 1 Gene (GhPPD1) in Cotton (Gossypium hirsutum L.) - Tao Zhou; Rui Zhang; Maozhi Ren; Shasha Zhang; Qin Lin; Sandui Guo (Plant Molecular Biology Reporter, 2013)

Molecular characterization of Chinese Hop stunt viroid isolates reveals a new phylogenetic group and possible cross transmission between grapevine and stone fruits - Zhixiang Zhang; Ying Zhou; Rui Guo; Lingxiao Mu; Yuanai Yang; Shifang Li; Hongqing Wang (European Journal of Plant Pathology, 2012)

Molecular Cloning and Characterization of GhGolS1, a Novel Gene Encoding Galactinol Synthase from Cotton (Gossypium hirsutum) - Tao Zhou; Rui Zhang; Sandui Guo (Plant Molecular Biology Reporter, 2012)

Characterization of a spliced variant of human IRF-3 promoter and its regulation by the transcription factor Sp1 - Wei Ren; Liang-Hua Zhu; Hua-Guo Xu; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2012)

A New Piezochromic Fluorescence and Aggregation-Induced Emission Compound Containing Tetraphenylethylene and Triphenylamine Moieties with Morphology-alterable Property - Xie Zhou; Hai-yin Li; Zhen-guo Chi; Bing-jia Xu; Xi-qi Zhang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2012)

Transcriptional control of human CD2AP expression: the role of Sp1 and Sp3 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2012)

Characterization of a novel isoform of the human ORMDL3 gene - Rui Jin; Wen-Xiao Yuan; Hua-Guo Xu; Wei Ren; Li-Li Zhuang; Guo-Ping Zhou (Cell and Tissue Research, 2011)

Olig1 and ID4 interactions in living cells visualized by bimolecular fluorescence complementation technique - Shu-Jun Guo; Jian-Guo Hu; Bao-Ming Zhao; Lin Shen; Rui Wang; Jian-Sheng Zhou; He-Zuo Lü (Molecular Biology Reports, 2011)

The characterization of two novel IRF-3 transcripts starting from intron 2 of the wild type of IRF-3 - Wei Ren; Hua-Guo Xu; Chao Lu; Rui Jin; Li Zou; Yi Wang; Guo-Ping Zhou (Molecular Biology Reports, 2011)

Synthesis and Characterization of Triphenylethylene Derivatives with Aggregation-Induced Emission Characteristics - Xiao-Fang Li; Zhen-Guo Chi; Bing-Jia Xu; Hai-Yin Li; Xi-Qi Zhang; Wei Zhou; Yi Zhang; Si-Wei Liu; Jia-Rui Xu (Journal of Fluorescence, 2011)

Construction of the yeast whole-cell Rhizopus oryzae lipase biocatalyst with high activity - Mei-ling Chen; Qin Guo; Rui-zhi Wang; Juan Xu; Chen-wei Zhou; Hui Ruan; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2011)

Molecular cloning and characterization of GhAPm, a gene encoding the μ subunit of the clathrin-associated adaptor protein complex that is associated with cotton (Gossypium hirsutum) fiber development - Tao Zhou; Rui Zhang; Dawei Yang; Sandui Guo (Molecular Biology Reports, 2011)

Direct repression of the human IRF-3 promoter by E2F1 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Immunogenetics, 2011)

Multiple amino acid variations in the nonstructural proteins of swine Japanese encephalitis virus alter its virulence in mice - Rui Wu; Yongxiang Tian; Junhua Deng; Keli Yang; Wangwang Liang; Rui Guo; Zhengying Duan; Zewen Liu; Danna Zhou; Diping Xu (Archives of Virology, 2011)

A three-dimensional finite element model of the cervical spine: an investigation of whiplash injury - Jian-Guo Zhang; Fang Wang; Rui Zhou; Qiang Xue (Medical & Biological Engineering & Computing, 2011)

Synthesis and Properties of Diphenylcarbazole Triphenylethylene Derivatives with Aggregation-Induced Emission, Blue Light Emission and High Thermal Stability - Bing-jia Xu; Zhen-guo Chi; Xiao-fang Li; Hai-yin Li; Wei Zhou; Xi-qi Zhang; Cheng-cheng Wang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Comparison of Responsive Behaviors of Two Cinnamic Acid Derivatives Containing Carbazolyl Triphenylethylene - Xi-qi Zhang; Zhen-guo Chi; Bing-jia Xu; Hai-yin Li; Wei Zhou; Xiao-fang Li; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Gene expression profiles of adipose tissue of high-fat diet-induced obese rats by cDNA microarrays - Jie Qiu; Rui Cheng; Xiao-yu Zhou; Jin-gai Zhu; Chun Zhu; Da-ni Qin; Chun-zhao Kou; Xi-rong Guo (Molecular Biology Reports, 2010)

MicroRNA-17 post-transcriptionally regulates polycystic kidney disease-2 gene and promotes cell proliferation - Huan Sun; Qing-Wei Li; Xiao-Yan Lv; Jian-Zhong Ai; Qiu-Tan Yang; Jing-Jing Duan; Guo-Hui Bian; Yan Xiao; Yi-Dong Wang; Zheng Zhang; Yu-Hang Liu; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

A missense mutation in the transmembrane domain of CESA4 affects protein abundance in the plasma membrane and results in abnormal cell wall biosynthesis in rice - Baocai Zhang; Lingwei Deng; Qian Qian; Guangyan Xiong; Dali Zeng; Rui Li; Longbiao Guo; Jiayang Li; Yihua Zhou (Plant Molecular Biology, 2009)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Transcriptional suppression of IE180 and TK promoters by the EP0 of pseudorabies virus strains Ea and Fa - Hong Guo; Rui Zhou; Yang Xi; Shaobo Xiao; Huanchun Chen (Virus Genes, 2009)

One of the possible mechanisms for the inhibition effect of Tb(III) on peroxidase activity in horseradish (Armoracia rusticana) treated with Tb(III) - Shaofen Guo; Rui Cao; Aihua Lu; Qing Zhou; Tianhong Lu; Xiaolan Ding; Chaojun Li; Xiaohua Huang (JBIC Journal of Biological Inorganic Chemistry, 2008)

Insulin inhibits β-adrenergic action in ischemic/reperfused heart: a novel mechanism of insulin in cardioprotection - Qiu-Jun Yu; Rui Si; Ning Zhou; Hai-Feng Zhang; Wen-Yi Guo; Hai-Chang Wang; Feng Gao (Apoptosis, 2008)

Loop-mediated isothermal amplification for rapid detection of Bacillus anthracis spores - Yan-Mei Qiao; Yong-Chao Guo; Xian-En Zhang; Ya-Feng Zhou; Zhi-Ping Zhang; Hong-Ping Wei; Rui-Fu Yang; Dian-Bing Wang (Biotechnology Letters, 2007)

Grifolin induces apoptosis via inhibition of PI3K/AKT signalling pathway in human osteosarcoma cells - Song Jin; Rui-Ping Pang; Jing-Nan Shen; Gang Huang; Jin Wang; Jia-Guo Zhou (Apoptosis, 2007)

Double-strand hydrolysis of DNA by a magnesium(II) complex with diethylenetriamine - Pin Yang; Rui Ren; Maolin Guo; Aixin Song; Xiangli Meng; Caixia Yuan; Qinghua Zhou; Huili Chen; Zhenhai Xiong; Xiaoli Gao (JBIC Journal of Biological Inorganic Chemistry, 2004)